2000
DOI: 10.1096/fj.00-0151fje
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning regulation of bcl‐2 and p66shc by human NOS1 enhances tolerance to oxidative stress

Abstract: Preconditioning stress induced by a transient ischemia may increase brain tolerance to oxidative stress, and the underlying neuroprotective mechanisms are not well understood. In a series of experiments, we found that endogenous nitric oxide (NO), S-nitrosoglutathione (GSNO), and antioxidants blocked serum deprivation-induced oxidative stress and apoptosis in human neuroblastoma cells. Similar to nuclear redox factor-1 (Ref-1), mRNA of human neuronal nitric oxide synthase (hNOS1) was maximally up-regulated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 44 publications
6
89
1
Order By: Relevance
“…Evidences from in vitro and in vivo studies suggested that Bcl-2 might block the apoptosis through the regulation of cellular antioxidant defense mechanisms and, in this context, had been considered to act as a free radical scavenger (Andoh et al, 2000). For instance, the levels of hydroxyl radicals generated by quinoneproducing agents and 3-nitropropionic acid were lowered in Bcl-2-overexpressing cells compared with the vector-transfected control cells (Luanpitpong et al, 2011;Yin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Evidences from in vitro and in vivo studies suggested that Bcl-2 might block the apoptosis through the regulation of cellular antioxidant defense mechanisms and, in this context, had been considered to act as a free radical scavenger (Andoh et al, 2000). For instance, the levels of hydroxyl radicals generated by quinoneproducing agents and 3-nitropropionic acid were lowered in Bcl-2-overexpressing cells compared with the vector-transfected control cells (Luanpitpong et al, 2011;Yin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…28 Moreover, in dilated cardiomyopathy, which is associated with increased levels of oxidative stress-mediated cell death, p66…”
Section: Discussionmentioning
confidence: 99%
“…Reconstitution of wild type p66 shc expression in these cells increases their sensitivity to hydrogen peroxide, while cells expressing mutant forms of the protein that cannot be serine phosphorylated behave like null cells (Migliaccio et al, 1999). In a different model system, Andoh et al (2000) showed that the downregulation of p66 shc caused by serum starvation and concomitant with an upregulation of the antiapoptotic Bcl-2 was associated with enhanced tolerance to oxidative challenges. Taken together, these data suggest that p66 shc is a crucial component of the apoptotic response to oxidative damage (reviewed in Lithgow and Andersen, 2000;Skulachev, 2000).…”
Section: Other Signaling Molecules and Pathways Jak/stat Pathwaymentioning
confidence: 99%